Relationship between Immunization Completeness and of Stunting in Under Five Years Old Children - Hanggi Hendri Hartia; Rita Kartika Sari (Journal of Economics and Public Health, 2026)
Stunting is problem global health that is hampering development children, where the prevalence in Indonesia (21.6%) is still above the WHO target (20%). District Pati, especially the work area Community Health Center Gabus II, has prevalence sufficient stunting significant that is by 20.28%. One of them effort prevention stunting is through giving immunization base complete. For know connection between completeness immunization toddler with incident stunting in the work area Community Health Center Gabus II Regency Starch. Type this research is studies observational with design research conducted at the Community Health Center Cork II. Sample study totaling 76 toddlers, consisting of from group cases and controls. Data were collected through questionnaires and notes KIA book, then analyzed using statistical tests Chi-Square. Analysis bivariate show existence significant relationship between completeness immunization with incident stunting with mark p-value 0.010 (p < 0.05). The Odds Ratio (OR) value of 0.000 (95% CI: 0.113-0.759) indicates that immunization base complete play a role as factor protector to incident stunting. There is connection between completeness immunization toddler with incident stunting in the work area Community Health Center Gabus II Regency Pati. Toddlers who get immunization base complete own risk more low For experience stunting compared to toddler with immunization No complete.